2016
DOI: 10.1111/add.13505
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of clinical AUDIT-C alcohol screening scores and changes in scores for three objective alcohol-related outcomes in a Veterans Affairs population

Abstract: When AUDIT-C screening is conducted in clinical settings, baseline AUDIT-C scores and score increases to moderate-severe alcohol misuse at follow-up screening appear to have predictive validity for HDL cholesterol, alcohol-related gastrointestinal hospitalizations and physical trauma. Decreasing AUDIT-C scores collected in clinical settings appear to have predictive validity for only HDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 60 publications
4
38
0
Order By: Relevance
“…Findings from this national study are consistent with prior studies that have found that alcohol use is associated with HIV control (Justice et al, 2016; Williams et al, 2016a) and with a previous study in general outpatients that found increases in drinking over time were associated with higher probability of subsequent gastrointestinal bleeding and trauma (Bradley et al, 2016). Findings from this study also complement those from the previous longitudinal study that assessed a scaled composite measure of HIV disease severity (Justice et al, 2012; Justice et al, 2013) using group-based trajectory analyses and identified the greatest likelihood of extreme HIV disease severity over time among a group of PLWH with consistent heavy alcohol use (Marshall et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings from this national study are consistent with prior studies that have found that alcohol use is associated with HIV control (Justice et al, 2016; Williams et al, 2016a) and with a previous study in general outpatients that found increases in drinking over time were associated with higher probability of subsequent gastrointestinal bleeding and trauma (Bradley et al, 2016). Findings from this study also complement those from the previous longitudinal study that assessed a scaled composite measure of HIV disease severity (Justice et al, 2012; Justice et al, 2013) using group-based trajectory analyses and identified the greatest likelihood of extreme HIV disease severity over time among a group of PLWH with consistent heavy alcohol use (Marshall et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Based on possible social desirability bias in reporting reduced drinking, and because previous research among general outpatients demonstrated that decreases in alcohol use were not consistently associated with improvements in medical outcomes in the following year while increases were associated with increased risk of diverse medical outcomes (Bradley et al, 2016), we hypothesized that increases in AUDIT-C scores would be associated with decreases in HIV control, whereas decreases in AUDIT-C score may not be reflected in outcomes. To test these hypotheses, we tested a priori -specified contrasts to assess for differences in the mean change in CD4 and mean change in logVL associated with an increase in AUDIT-C by 2 points (AUDIT-C change score −2) vs. remaining stable (AUDIT-C change score 0); we similarly compared an increase in AUDIT-C by 5 points (AUDIT-C change −5) to remaining stable (AUDIT-C change 0) and an increase in AUDIT-C by 5 points (AUDIT-C change −5) to increased AUDIT-C by 8 points (AUDIT-C change −8).…”
Section: Methodsmentioning
confidence: 99%
“…They also reviewed screens and brief instruments administered during the CHOICE baseline assessment (Table 2) [86–89, 114116] and alcohol biomarker results: GGT, CDT, and red cell mean corpuscular volume (MCV) [117, 118]. …”
Section: Methodsmentioning
confidence: 99%
“…Alcohol-related disorders were investigated using the Audit-C scale, a validated and effective questionnaire for predicting hazardous alcohol drinking [21,2831], as prescribed by Italian legislative decree n. 81; it was administered to the participants after a medical examination at the ambulatory. The Audit-C questionnaire employed was a shortened version incorporating only the first three questions: 1) How often do you consume alcoholic drinks?…”
Section: Methodsmentioning
confidence: 99%